The badjao mendicancy in Iloilo City. - Cubing, Genevieve B. (2003.)
This study seeks to give a descriptive account of Badjao mendicancy in IloiloCity; The causes of their migration, reasons for choosing Iloilo, their new way of life and the Government's response to the problem they brought in Iloilo., There were only fifteen (15) Badjaos who were interviewed because they were the ones who can understand Hiligaynon; some preferred Cebuano and Tagalog. They were asked certain questions concerning their presence here and the mendicancy issue. They were interviewed in their resting places at the 1985 Tan-Guzman Bldg. in corner Guanco-Muelle Loney St. and in the Iloilo Che Young Coa and Chua Association Bldg. in Aldeguer-Muelle Loney. The interview and observations were done during late afternoons and early evening since these are the usual times when the Badjaos returned to their places. The personnel of the National Commission on Indigenous People who were assigned to the Badjaos were the key informants about the actions taken by the local government officials. Mrs. Josela Gregorio, a National Commission on Indigenous People employee, the former Chairman of the Task Force Badjao was requested if the documents about Badjaos can be studied. The other NCIP employee was Mrs. Agnes Coronado who assisted the researcher by giving the side of the government on the issue of Badjao mendicancy. It was found out that the Badjaos accused the "Abu Sayaffs" of killing their families and seizing their properties. They said it was the major reason for their coming here to beg. They actually came here by batch or by families from Sulu and Basilan. Due to their increasing number in Iloilo, there were problems they created fort he city. One of the most serious complaints of the Illongos is the waste they contribute to the city. They do not have proper disposal of their wastes making the area they occupy in the city stink and an eyesore. The traffic enforcers, jeepney drivers and passengers are complaining of the delay and danger caused by the Badjaos mendicants. In response to the problems caused by the Badjaos, the government officials with other government agencies like the NCIP, the Iloilo City Social Welfare and Development Office, City Health Office, Commision on Human Rights, Philippine Coast Guard, Philippine Air Force City Police Office, Office of Muslim Affairs and the City Tourism Office created the Special Task Force Badjaos. It aimed to study and evaluate the case in order for them to take the necessary actions to solve the problem. The first action was the deportation of the badjaos by batch and the second action was the proposed temporary settlement in Guimaras. But the government officials still prefer deportation as the solution to the problem for a reason. It was stated in the Indigenous Peoples Rights Act of 1997 that the provision under this is on the premise that the People Rights Act of 1997 that the provision under this is on the premise that the indigenous people is on their ancestral land. Their rights are to be protected by the government of Sulu and Basilan, not the government of Iloilo City. The Badjao mendicancy is still prevalent and the government officials are continuing to devise plans that will solve the problem.
Research Project (Undergraduate, Bachelor of Arts in History) College of Arts and Sciences, UP Visayas, Miagao, Iloilo
Keywords: Badjao